The public health issues of the Muslim countries - Wan Su, Kamaruzaman (2011)
It is estimated that 1.2 to 1.57 billion Muslim populate the world which is about 23% of the world 6.8 billion population in 2009 (which is about one fifth of the world population). Muslim are the majority in 57 countries which form an inter-governmental orgainzation called the Organizational of Islamic Conference (OIC). From the 6th to the 15th century AD, Islamic civilization was considered to be the most advance, tolerant and progressive civilization in the world because their accomplishments in all discipline of knowledge. The Muslim scientists made significant advances in the sciences placing far greater emphasis on experiment than had the Greek, beginning with the scientific method of Ibn al-Haytham on optics 1000 years ago. But after the 16th century AD, the situation changed drastically, when learning and inquiry was no longer the motto of the Muslims resulting in the lowest status of economy and health in the Muslim countries. A study on the status of Democracy Index was done among 48 of the 57 OIC countries, found out that Muslim countries have an average unemployement rate of 15.44% and a military expenditure as percentage of GDP of 4.93 % (S.Sarsar and D.B Strohmetz 2008). This paper tries to look into the Public Health status of thesess countries by comparing the life expactancy at birth, the infant mortality rate, the maternal mortality rate and the toddler mortality rate to the status of Democracy Index.